Will the circle be unbroken? : reflections on death, rebirth, and hunger for a faith. - Terkel, Studs (New York : New Press, 2014)
From interviews with a Hiroshima survivor, AIDS caseworker, death-row parolee, police, firefighters, emergency health workers, doctors, nurses, writers, undertakers, clergy, etc., etc.
Includes bibliographical references.
Keywords: Death; Death -- Religious aspects; Death; Death -- Religious aspects